PENENTUAN PORTOFOLIO OPTIMAL BERDASARKAN MODEL MARKOWITZ PADA PERUSAHAAN INFRASTRUKTUR DI BURSA EFEK INDONESIA - Mahayani, Ni Putu Mega; Suarjaya, A. A. Gede (E-Jurnal Manajemen, 2019)
Investment growth continues to increase every year, no exception to the stock investment instruments. In investing, investors expect the highest return with certain risks that are willing to be borne. This study aims to find out which stocks are included in the optimal portfolio combination, along with the proportion of each fund that will signal the expected return and portfolio risk. The study was conducted on the IDX in the shares of infrastructure, utilities and transportation sector companies for the period of January-December 2017. The data used in the study were secondary data obtained from www.idx.co.id and www.finance.yahoo.com. The sample in the study was the infrastructure, utility, and transportation sector companies which provided a positive expected return during the study period. The results of the study showed that from 31 samples there were 23 stocks that were included in the determination of the optimal portfolio of the Markowitz model. Consists of shares of AKSI, BALI, BUKK, CMNP, CMPP, EXCL, IBST, KOPI, META, NELY, OASA, POWR, RAJA, RIGS, SAFE, SDMU, SHIP, SMDR, TBIG, TLKM, TOWR, TRAM, and WINS. Provide a portfolio expected return of 5.085 percent with a portfolio risk of 0.004 percent. Keywords: Stock Investment, Optimal Portfolio, Markowitz Model